Approaches to mixture risk assessment of PFASs in the European population based on human hazard and biomonitoring data - W. Bil; E. Govarts; M.J. Zeilmaker; M. Woutersen; J. Bessems; Y. Ma; C. Thomsen; L.S. Haug; S. Lignell; I. Gyllenhammar; L. Palkovicova Murinova; L. Fabelova; et al. (International Journal of Hygiene and Environmental Health, 2023)

From science to policy: How European HBM indicators help to answer policy questions related to phthalates and DINCH exposure - Antje Gerofke; Madlen David; Phillipp Schmidt; Joana Lobo Vicente; Jurgen Buekers; Liese Gilles; Ann Colles; Jos Bessems; Michiel Bastiaensen; Adrian Covaci; Elly Den Hond; Gudrun Koppen; et al. (International Journal of Hygiene and Environmental Health, 2023)

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The Future of Midlatitude Cyclones - Jennifer L. Catto; Duncan Ackerley; James F. Booth; Adrian J. Champion; Brian A. Colle; Stephan Pfahl; Joaquim G. Pinto; Julian F. Quinting; Christian Seiler (Current Climate Change Reports, 2019)
Purpose of Review This review brings together recent research on the structure, characteristics, dynamics, and impacts of extratropical cyclones in the future. It draws on research using idealized models and complex climate simulations, to evaluate what is known and unknown about these future changes. Recent Findings There are interacting processes that contribute to the uncertainties in future extratropical cyclone changes, e.g., changes in the horizontal and vertical structure of the atmosphere and increasing moisture content due to rising temperatures. Summary While precipitation intensity will most likely increase, along with associated increased latent heating, it is unclear to what extent and for which particular climate conditions this will feedback to increase the intensity of the cyclones. Future research could focus on bridging the gap between idealized models and complex climate models, as well as better understanding of the regional impacts of future changes in extratropical cyclones.

Genome‐wide association of functional traits linked with C ampylobacter jejuni survival from farm to fork - Koji Yahara; Guillaume Méric; Aidan J. Taylor; Stefan P. W. de Vries; Susan Murray; Ben Pascoe; Leonardos Mageiros; Alicia Torralbo; Ana Vidal; Anne Ridley; Sho Komukai; Helen Wimalarathna; et al. (Environmental Microbiology, 2017)
Summary Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.

Natural killer cells in acute myeloid leukemia patients: from phenotype to transcriptomic analysis - G. Venton; Y. Labiad; J. Colle; A. Fino; S. Afridi; M. Torres; S. Monteuil; B. Loriod; N. Fernandez-Nunez; L. Farnault; P. Suchon; J. C. Mattei; et al. (Immunologic Research, 2016)

Carotene Degradation and Isomerization during Thermal Processing: A Review on the Kinetic Aspects - Ines J. P. Colle; Lien Lemmens; Griet Knockaert; Ann Van Loey; Marc Hendrickx (Critical Reviews in Food Science and Nutrition, 2016)

The long‐term dynamics of C ampylobacter colonizing a free‐range broiler breeder flock: an observational study - Frances M. Colles; Noel D. McCarthy; Carly M. Bliss; Ruth Layton; Martin C. J. Maiden (Environmental Microbiology, 2015)
Summary A free‐range broiler breeder flock was studied in order to determine the natural patterns of C ampylobacter colonization over a period of 63 weeks. C ampylobacter sequence types ( STs ) were not mutually exclusive and on average colonized only 17.7% of the birds tested at any time. C ampylobacter STs typically reached a peak in prevalence upon initial detection in the flock before tailing off, although the ST and antigenic flaA short variable region in combination were stable over a number of months. There was evidence that, with a couple of exceptions, the ecology of C . jejuni and C . coli differed, with the latter forming a more stable population. Despite being free range, no newly colonizing STs were detected over a 6‐week period in autumn and a 10‐week period in winter, towards the end of the study. There was limited evidence that those STs identified among broiler chicken flocks on the same farm site were likely to colonize the breeder flock earlier ( R 2 0.16, P 0.01). These results suggest that there is natural control of C ampylobacter dynamics within a flock which could potentially be exploited in designing new intervention strategies, and that the two different species should perhaps be considered separately.

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Marked host specificity and lack of phylogeographic population structure of Campylobacter jejuni in wild birds - Petra Griekspoor; Frances M. Colles; Noel D. McCarthy; Philip M. Hansbro; Chris Ashhurst‐Smith; Björn Olsen; Dennis Hasselquist; Martin C. J. Maiden; Jonas Waldenström (Molecular Ecology, 2013)
Zoonotic pathogens often infect several animal species, and gene flow among populations infecting different host species may affect the biological traits of the pathogen including host specificity, transmissibility and virulence. The bacterium Campylobacter jejuni is a widespread zoonotic multihost pathogen, which frequently causes gastroenteritis in humans. Poultry products are important transmission vehicles to humans, but the bacterium is common in other domestic and wild animals, particularly birds, which are a potential infection source. Population genetic studies of C. jejuni have mainly investigated isolates from humans and domestic animals, so to assess C. jejuni population structure more broadly and investigate host adaptation, 928 wild bird isolates from Europe and Australia were genotyped by multilocus sequencing and compared to the genotypes recovered from 1366 domestic animal and human isolates. Campylobacter jejuni populations from different wild bird species were distinct from each other and from those from domestic animals and humans, and the host species of wild bird was the major determinant of C. jejuni genotype, while geographic origin was of little importance. By comparison, C. jejuni differentiation was restricted between more phylogenetically diverse farm animals, indicating that domesticated animals may represent a novel niche for C. jejuni and thereby driving the evolution of those bacteria as they exploit this niche. Human disease is dominated by isolates from this novel domesticated animal niche.

Progressive genome‐wide introgression in agricultural Campylobacter coli - Samuel K. Sheppard; Xavier Didelot; Keith A. Jolley; Aaron E. Darling; Ben Pascoe; Guillaume Meric; David J. Kelly; Alison Cody; Frances M. Colles; Norval J. C. Strachan; Iain D. Ogden; Ken Forbes; et al. (Molecular Ecology, 2013)
Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens C ampylobacter coli and C . jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA . Members of this lineage belong to two groups, the ST ‐828 and ST ‐1150 clonal complexes. The ST ‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA . By contrast, the more commonly isolated ST ‐828 complex bacteria have 10–11% introgressed DNA , and C. jejuni and nonagricultural C. coli lineages each have C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli . These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.

Specialists leave fewer descendants within a region than generalists - Wim A. Ozinga; Audrey Colles; Igor V. Bartish; Françoise Hennion; Stephan M. Hennekens; Sandrine Pavoine; Peter Poschlod; Marie Hermant; Joop H. J. Schaminée; Andreas Prinzing (Global Ecology and Biogeography, 2013)
Aim Current conservation biology suggests that across ecological time‐scales specialist species existing in the recent past have left on average fewer descendant populations today than generalist species. Conversely, the speciation literature suggests that on an evolutionary time‐scale specialists leave as many or more descendant lineages as generalists, i.e. they have high rates of global diversification. This begs the question: which of these two processes has more influence on the regional scale, i.e. do specialists leave more or fewer descendants than generalists within a region? Location The flora of the N etherlands. Methods We quantified niche volume of 707 plant species from coexistence data and ecological indicator values and used sister taxon comparisons to compare specialist and generalist sister taxa for the relative numbers of descendants across three temporal scales: ecological, microevolutionary and macroevolutionary. Results We show, first, that specialist species are more likely to be currently declining, i.e. to leave only few descendant populations. Second, specialists are less likely to be currently diversifying into intra‐specific taxa. Finally, most specialist clades left fewer descendant species within a region than their generalist sister clades. These results were consistent across sublineages, unbiased by geographic sampling of lineages and environments, and held after accounting for species life histories. Differences between specialist and generalist sister clades increased with clade age, suggesting that they reflect differences in rates at which specialists left descendants (rather than differences in ecological limits to the numbers of specialists and generalists). Main conclusions Specialists left only few descendants within a region (i.e. the N etherlands), both at ecological, microevolutionary and macroevolutionary scales. While specialists may leave numerous evolutionary descendants at a global scale, these might be absent from most regions. Humans, by threatening specialist species, may hence further accelerate biotic homogenization with descendants of generalist lineages proliferating within regions while specialist lineages disappear.

Niche segregation and genetic structure of Campylobacter jejuni populations from wild and agricultural host species - SAMUEL K. SHEPPARD; FRANCES M. COLLES; NOEL D. McCARTHY; NORVAL J. C. STRACHAN; IAIN D. OGDEN; KEN J. FORBES; JOHN F. DALLAS; MARTIN C. J. MAIDEN (Molecular Ecology, 2011)
Bacterial populations can display high levels of genetic structuring but the forces that influence this are incompletely understood. Here, by combining modelling approaches with multilocus sequence data for the zoonotic pathogen Campylobacter, we investigated how ecological factors such as niche (host) separation relate to population structure. We analysed seven housekeeping genes from published C. jejuni and C. coli isolate collections from a range of food and wild animal sources as well as abiotic environments. By reconstructing genetic structure and the patterns of ancestry, we quantified C. jejuni host association, inferred ancestral populations, investigated genetic admixture in different hosts and determined the host origin of recombinant C. jejuni alleles found in hybrid C. coli lineages. Phylogenetically distinct C. jejuni lineages were associated with phylogenetically distinct wild birds. However, in the farm environment, phylogenetically distant host animals shared several C. jejuni lineages that could not be segregated according to host origin using these analyses. Furthermore, of the introgressed C. jejuni alleles found in C. coli lineages, 73% were attributed to genotypes associated with food animals. Our results are consistent with an evolutionary scenario where distinct Campylobacter lineages are associated with different host species but the ecological factors that maintain this are different in domestic animals such that phylogenetically distant animals can harbour closely related strains.

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Campylobacter infection of broiler chickens in a free‐range environment - Frances M. Colles; Tracey A. Jones; Noel D. McCarthy; Samuel K. Sheppard; Alison J. Cody; Kate E. Dingle; Marian S. Dawkins; Martin C. J. Maiden (Environmental Microbiology, 2008)
Summary Campylobacter jejuni is the most common cause of bacterial gastroenteritis worldwide, with contaminated chicken meat considered to represent a major source of human infection. Biosecurity measures can reduce C. jejuni shedding rates of housed chickens, but the increasing popularity of free‐range and organic meat raises the question of whether the welfare benefits of extensive production are compatible with food safety. The widespread assumption that the free‐range environment contaminates extensively reared chickens has not been rigorously tested. A year‐long survey of 64 free‐range broiler flocks reared on two sites in Oxfordshire, UK, combining high‐resolution genotyping with behavioural and environmental observations revealed: (i) no evidence of colonization of succeeding flocks by the C. jejuni genotypes shed by preceding flocks, (ii) a high degree of similarity between C. jejuni genotypes from both farm sites, (iii) no association of ranging behaviour with likelihood of Campylobacter shedding, and (iv) higher genetic differentiation between C. jejuni populations from chickens and wild birds on the same farm than between the chicken samples, human disease isolates from the same region and national samples of C. jejuni from chicken meat.